Industrial Relations Dispute Resolution Model in Indonesia - Widyastuti, Tiyas Vika; Soponyono, Eko; Hamzani, Achmad Irwan; Bawono, Bambang Tri; Mashdurohatun, Anis (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to find out and examine industrial relations dispute resolution models in Indonesia. This research is normative legal research using a qualitative approach. The results of the research show that there are several types of disputes, namely Rights Disputes, Interest Disputes, Termination of Employment Disputes (PHK), Disputes between Trade Unions/Labor Unions. The author took the example of the case of PT Holcim Indonesia Tbk's unilateral layoff of its employees which was resolved through litigation in court. Industrial relations. With the enactment of Law Number 2 of 2004 concerning Settlement of Industrial Relations Disputes, there is a guarantee of protection for workers regarding the basic rights of workers/laborers and guarantees of equality, opportunity and equal treatment without discrimination on any basis.